Sustainable Development Guideline School Administration for Morality Restoration by Buddhist Ways: Tavanchaividhaya School - เทศสมบูรณ์ สุรพี; ภูมิโคกรักษ์ พิกุล (Ratchaphruek Journal, 2018)
ABSTRACT The research purpose are to study 1) opinion of participants in school administration, and 2) sustainable development guideline Tavanchaividhaya school administration for morality restoration by Buddhist ways. This is amixed methods research, and divided into 2 steps; 1) to study opinion of participants in school administration by rating scale questionnaire. Samples group studied were 205 participants in school administration. There are4 groups include; 1) 7 school boards and consultants, 2) 17 teachers and staff, 3) 83 parents, 4) 98 school sponsors. The statistic used for the analysis of the study were percentage, mean ( ), Standard Deviation (S.D.). Result of the study revealed the opinion of participants in school administration overall, were considerable at the highest level. When considering in each side, found it was the highest level is staff, followed by skills, strategy and systems, 2)to study the sustainable development guideline school administration by focus group. The result of the research, were1) Staff: to focus on the screening by moral standards and personality development of teachers, 2) Skills: To inspire and have positive attitude towards the development of students’ moral standards, 3) Strategy: to focus on creating the environment to developmental learning by universal goodness. Moral teaching must be evident in both theory and practice in accordance with morality based by Buddhist way, 4) Systems: To define in compliance with the standards universal goodness and be a master at inspiring the students willingly accepted by faith, 5) Style: To determine of management style that represents Ideology to create leader, give precedence and attentive to cultivate morality by universal goodness, 6) To shared values: be specify standards of universal goodness, inspire and develop cooperation continuously, apply universal goodness to cultivate in lifestyle, and 7) Structure: To add especially department for student development life skills and moral standard, and create a network to support educational resources.